Family as a generator of social capital: the role of family associations in Italy - Cimagalli, Folco (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
The Italian welfare system is looking for new models. In fact, the current system has lived through some years of structural crisis which has several causes: excessive rigidity, inadequacy to respond to the new social demands, the inability to sustain ever increasing costs. It is not easy to imagine what will be the welfare model of 2020: one of the possible hypotheses in the field is the development of the so-called “fourth sector”, represented in a particular way by the family associations. It is a relatively recent phenomenon, which draws, in the national outlook, increasing attention and significant development. The family, in this context, takes on a new role: not just a recipient of political attention, but a true engine of action and change. The central feature of this phenomenon is the self-help between families which have common problems and which identify common practices. The paper reconstructs the outline of the phenomenon in the national context and suggests working paths for social policies. The family associations, as activators of social relationships between people and groups, are a generator of social capital. In this sense, they are an essential resource for a new type of welfare: no longer based on a combination of need/service, but truly able to be generative.
Keywords: family associations; social capital; welfare; Italy; disabled people